Making the leap from drought monitoring to managing agricultural drought risks in India (WLE-IWMI) - CGIAR Research Program on Water, Land and Ecosystems (2018)
The South Asia Drought Monitoring System (SADMS), created by the CGIAR Research Program on Water, Land and Ecosystems (WLE) and partners, provided real-time drought severity data at micro-level to three Indian districts. The crop yields and incomes in these areas were significantly higher than in the control areas. As a result, the Indian government and World Bank plan to scale out the model.